Genetic Perspectives on Feed Event, Meal and Feed Efficiency Traits in Bos taurus indicus Beef Cattle - Valente, Júlia de Paula Soares [UNESP]; Mota, Lúcio Flávio Macedo [UNESP]; Rodrigues, Gustavo Roberto Dias [UNESP]; Deniz, Matheus [UNESP]; Malheiros, Jessica Moraes; Canesin, Roberta Carrilho; Dias, Laila Talarico; Costa, João Henrique Cardoso; Mercadante, Maria Eugênia Zerlotti [UNESP] (Wiley, 2025)
Electronic feeders record feeding behaviour as feed events by tracking the animal's in-out visits to the feeder. Another way to measure feeding behaviour is based on meals. However, the two approaches provide different outcomes. The objectives of this study were to estimate genetic parameters (heritabilities and genetic and phenotypic correlations) for feed event and meal traits, and their genetic and phenotypic correlations with feed efficiency traits in Nellore cattle. The present study analysed six feed event traits (DMIFE: dry matter intake per feed event, FED: feed event duration, TBFE: time between feed events, FTd: feeding time per day, FEd: feed events per day, and FR: feeding rate), six meal traits (DMIME: DMI per meal, MED: meal duration, TBME: time between meals, MC: meal criterion, MTd: meal time per day, and MEd: meals per day), and three feed efficiency traits (ADG: average daily gain, DMI, and RFI: residual feed intake). The traits were measured in feed efficiency tests of Nellore cattle (age = 280 ± 41 days and body weight = 258 ± 47 kg at enrolment). The MC was calculated for each animal and ranged from 1.70 to 64.0 min, i.e., any pair of feed events separated by less than the MC value was considered part of the same meal. The heritabilities and correlations were estimated by fitting univariate and bivariate animal models, respectively, using single-step genomic BLUP. The highest heritabilities for feed event traits were 0.35 ± 0.06 (FED), 0.39 ± 0.06 (FTd), and 0.50 ± 0.05 (FTd), and for meal traits were 0.31 ± 0.06 (MED) and 0.45 ± 0.06 (MTd). The genetic correlation between feed event traits and meal traits were weak. FR, FED, and FTd had moderate genetic correlations with RFI (−0.56 ± 0.11, 0.44 ± 0.11, 0.60 ± 0.08, respectively). These results indicate that more efficient animals spent less time at the feeder per feed event and per day, and eat faster compared to less efficient animals. In conclusion, feed event and meal traits must be treated as distinct groups of traits since the genetic and phenotypic correlations were, in general, weak to moderate. Among feed event versus meal traits, feed event traits are more favourable to explain the genetic relationships of feeding behaviour with feed efficiency-related traits.
Keywords: feeding behaviour; genetic parameters; meal criterion; Nellore cattle